(untitled) (Research, Society and Development, 2022)
This article aims to contextualize the existence of collective actions in the so-called institutionalized society, the product of mass phenomena present in the contemporary world, as well as to consolidate the conceptual perspective of these procedural instruments, contextualizing them before the commitment of the Constitutional State to the realization of access to justice through the effectiveness of jurisdiction. Thus, from a review of specialized bibliography, by qualitative research, we sought to demonstrate the applicability of contemporary proceduralism in the protection of transindividual rights through the presentation of public civil action, popular action and collective security warrant, starting from the corresponding constitutional foundations, in order to perceive the link between the existential purposes of each of these mechanisms and the commitment to collective rights in a broad sense. Therefore, with the inaugural theoretical support and the reading of the essential aspect of the rights protected by the three actions briefly examined, it concludes that collective actions show an increase even to the judicial function, since it becomes an institutional purpose to protect individual and collective rights, giving more effectiveness to the concept of jurisdiction, due process and the very idea of democracy as a regime in force in a rule of law attentive to reality and the demands of the collective.